A multifuncionalidade do aposto em textos jornalísticos de divulgação científica e em artigos científicos - Farias, Cristina Araújo de (2011)
The objective of this research is to examine the use of the bet, as noun phrase, and what is its function in the texts of scientific articles and journalist texts of scientific popularization. To this, we used the functional approach, which studies the linguistic expressions not separately, but according to the purposes that carry the texts. Thus, the bet is seen as discursive textual functions, unlike the traditional view of grammars, which define the term bet as an accessory, or unnecessary to understanding the message. The corpus consists of texts of scientific articles genres and journalistic texts of science popularization. The former were taken from journals of the Federal University of Rio de Janeiro - UFRJ, University of Campinas - UNICAMP and University of Sao Paulo - USP, and the latter were taken from newspapers published by the same institutions. After the selection of texts, we performed a quantitative analysis, which were highlighted in appositional constructions. The context of occurrence, the period in which the bet was, was copied to the analysis table, where were the parameters of analysis: classification of the fundamental bet in prayer position, score, prior to the connective I bet, for textual and semantic-textual-discursive function. It was found through qualitative analysis that affixed under the functionalist approach, features textual discourse, it is an aid to referral, a process that by reconstructing the objects-of-world in objects-of-speech in the act communicative, demonstrates that there is no direct relationship between words and things in the world. In the case of the bet, this reconstruction serves as a container that is placed on a term for the perception of who receives the message is the same man who has produced. The strategy of argument is closely related to the referral strategy, as Perelman and Olbrechts-Tyteca (1996) the selection of words already indicates the intention of argument, whose character is being biased. Make the person receiving the message have the same approach to who produced it is a way of not allowing different understanding of him that want to have.